Proceedings. 'Meeting the Tests of Time'., International Test Conference
DOI: 10.1109/test.1989.82325
|View full text |Cite
|
Sign up to set email alerts
|

CMOS IC stuck-open-fault electrical effects and design considerations

Abstract: The electrical effects of CMOS IC physical defects that caused stuck-open faults are evaluated, including their voltage levels, quiescent power supply current (IDDQ), transient response, and important testing considerations. The transient responses of the defective node voltage and power supply current to the high impedance state caused by a stuck-open defect were measured to determine if the IDDQ measurement technique could detect stuck-open faults. technique does detect stuck-open faults in some designs, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Let us now observe the case when the average value is fixed and K is changed. In this case, when K=1, we obtain an exponential function as distinctly shown by Equation (2). As K is increased, it changes to a distribution with a peak at a location larger than 0.…”
Section: Detection Methods Using a Gamma Distribution Approximationmentioning
confidence: 70%
See 2 more Smart Citations
“…Let us now observe the case when the average value is fixed and K is changed. In this case, when K=1, we obtain an exponential function as distinctly shown by Equation (2). As K is increased, it changes to a distribution with a peak at a location larger than 0.…”
Section: Detection Methods Using a Gamma Distribution Approximationmentioning
confidence: 70%
“…F(x)= k / (K)×x K-1 e -x (0=<x< ) Average X=K/ , Variance 2 =K/ 2 (2) The assumption of a gamma distribution is based on the following reasoning. First, if the average value X and K are determined, then is determined unconditionally.…”
Section: Detection Methods Using a Gamma Distribution Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the SOF model was first proposed in [2], intensive research effort has been devoted to improving the characterization [3], testing [4]- [6], and diagnosis [9]- [12] of this class of faults. These studies have demonstrated its efficiency for a wide spectrum of technologies, including the deep submicrometer domain.…”
Section: Introductionmentioning
confidence: 99%
“…IDDQ testing has been shown to be an effective complement to standard stuck-at fault testing due to its ability to detect many of those defects that are not correctly modeled as stuck-at faults [6][7][8][9][10]. Moreover, elevated Iix~e has been shown to be a reliability hazard even when a device passes functional testing.…”
Section: Introductionmentioning
confidence: 99%